Effects of whole-body vibration training with different frequencies on the balance ability of the older adults: a network meta-analysis - Liu, Peirong; Li, Yongjie; Xiao, Yajun; Li, Duo; Liu, Lin; Ma, Yong; Zheng, Weitao (Frontiers in Physiology, 2023)
Purpose: To compare the effects of whole body vibration training (WBVT) with different frequencies on the balance ability of older adults. Methods: Randomized controlled trials (RCTs) on the WBVT interventions on balance ability in older adults were searched through PubMed, Web of Science, The Cochrane Library, ProQuest, Embase, China National Knowledge Infrastructure(CNKI), Wanfang, and China Science and Technology Journal Database(CSTJ) databases from the establishment of the database to August 2022. Two reviewers screened and assessed the risk quality of the included literature according to the physiotherapy evidence database (PEDro) scale criteria. Statistical analysis was performed using Stata 14.0 software after data extraction. Results: Twenty-five RCTs with a total of 1267 subjects were finally included. The results of the pairwise comparison of the Network Meta-analysis showed lower Timed Up and Go Test (TUGT) values for Low-frequency whole body vibration training (LF-WBVT) compared to the placebo and traditional rehabilitation groups [WMD=-1.37, 95% CI (-2.53, -0.20)] [WMD=-1.84, 95%CI(-3.17,-0.51)], the difference was statistically significant; Five-repetition Sit-to-Stand Test (5STS) values were lower for LF-WBVT, Medium frequency whole body vibration training (MF-WBVT) and High-frequency whole body vibration training (HF-WBVT). ,5STS) values were lower, but none were statistically significant. In addition, the TUGT and 5STS values of HF-WBVT tended to be lower than those of LF-WBVT and MF-WBVT, but neither of them was statistically different. The cumulative probability ranking results of both TUGT and 5STS showed that HF-WBVT was the best protocol. Conclusions: Current evidence shows that HF-WBVT may be the best protocol for improving balance in older adults. Due to the study's limitations, the conclusion obtained in this study still needs to be further confirmed by more high-quality studies.